Effects of intranasal oxytocin and positive couple interaction on immune factors in skin wounds - Ditzen, Beate; Aguilar-Raab, Corina; Winter, Friederike; Hernández, Cristóbal; Schneider, Ekaterina; Bodenmann, Guy; Heinrichs, Markus; Ehlert, Ulrike; Läuchli, Severin (Brain, behavior and immunity, 2023)
Intimate social relationships improve individual health and longevity, an effect which is supposed to be mediated through stress-sensitive endocrine and immune mechanisms in response to positive interaction behavior. On a neuroendocrine level, oxytocin (OT) buffers stress responses, modulates social attachment behavior and has been associated with cytokine expression. Consequently, the aim of the present study was to investigate instructed positive couple interaction, observed behavior, and OT in their effect on immune function.
Online veröffentlicht am 2. September 2022
Gesehen am 08.11.2023